Legal Policy Against People Smuggling as a Crime of Trafficking in Persons with a Transnational Dimension - Rizkan Zulyadi; Serimin Pinem; Andi Hakim Lubis; Nindya Dhaneswara (Jurnal Hukum, 2024)
This research investigates Indonesia’s legal framework for addressing human smuggling, focusing on the integration of penal policies targeting its root causes and evaluating the impact of international collaborations in law enforcement. Despite existing literature on human smuggling, critical gaps remain, particularly in understanding the role of criminal policy as part of social policy and the practical effects of international cooperation. The study aims to answer two primary questions: the role of criminal policy in addressing human smuggling crimes in Indonesia and the non-penal policies Indonesia has implemented to combat human smuggling. This research adopts a normative legal methodology, analyzing Indonesia’s Criminal Code, the Eradication of Trafficking in Persons Law, the Suppression of Migrant Smuggling Law, and relevant international frameworks like the Bali Process. The study reveals that an effective approach to combating human smuggling requires a balance of penal and non-penal measures, strong adherence to territorial sovereignty, and enhanced international cooperation. It finds that while penal policies act as deterrents, non-penal strategies, such as victim protection and public awareness campaigns, are equally crucial. Additionally, the study highlights the importance of regional and international collaborations in strengthening law enforcement, emphasizing the need for specialized legal framework to address human smuggling.